Assessment of a channel catfish population in a large open river system. (16th November 2017) - Blank, A. J.; Hamel, M. J.; Spurgeon, J. J.; Pegg, M. A.
Abstract: Estimates of dynamic rate functions for riverine channel catfish, Ictalurus punctatus (Rafinesque), populations are limited. The open nature and inherent difficulty in sampling riverine environments and the propensity for dispersal of channel catfish impede estimation of population variables. However, contemporary population models (i.e. robust design models) can incorporate the open nature of these systems. The purpose of this study was to determine channel catfish population abundance, survival and size structure and to characterise growth in the lower Platte River, Nebraska, USA. Annual survival estimates of adult channel catfish were 13%–49%, and channel catfish abundance estimates ranged from 8, 281 to 24, 261 fish within a 10‐km sampling reach. Channel catfish were predominantly (90%) <age 5 and <400 mm total length, and adult growth was similar to other populations across the species' range. The channel catfish population characteristics in the lower Platte River are likely a result of a combination of factors including recreational harvest and potential shifts in habitat during different life stages. A multifaceted sampling and analytical approach provided additional information such as movement and abundance estimates and may also help to decipher abiotic and biotic factors that interact when managing fish populations in riverine environments.